2023
DOI: 10.1057/s41599-023-01720-z
|View full text |Cite
|
Sign up to set email alerts
|

Subjective experience, self-efficacy, and motivation of professional football referees during the COVID-19 pandemic

Abstract: The present multi-study article investigates the subjective experience of professional football (a.k.a. soccer) referees and players during the COVID-19 pandemic and the so-called ghost games (i.e., games without supporters). Referees from the Austrian Football Association completed questionnaires inquiring about self-efficacy, motivation, and general personal observations and perceptions (e.g., arousal or confidence). In addition, two players and one referee in the Austrian Football Bundesliga were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Very high quality descriptive (Leitner & Richlan, 2021a) and high quality (Bordigon & Neto, 2022) studies were found, as well as very high quality predictive (Sors et al, 2021) and high quality studies (Wilkesmann, 2022). Medium quality theoretical (Webb, 2021) and very high quality (Richlan et al, 2023) studies were also found. An average number of good quality studies was found, but research should continue in different genders and categories to obtain greater variety and maintain study quality.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Very high quality descriptive (Leitner & Richlan, 2021a) and high quality (Bordigon & Neto, 2022) studies were found, as well as very high quality predictive (Sors et al, 2021) and high quality studies (Wilkesmann, 2022). Medium quality theoretical (Webb, 2021) and very high quality (Richlan et al, 2023) studies were also found. An average number of good quality studies was found, but research should continue in different genders and categories to obtain greater variety and maintain study quality.…”
Section: Discussionmentioning
confidence: 83%
“…In the predictive phase, a sizeable proportion (40%, n=12) similarly demonstrated decreased home advantage, but a higher percentage (22%, n=7) evidenced no fan-based differences. Among the theoretical works, three studies were unclassified since they did not include original data analysis (Gouveia & Pereira, 2021;Richlan et al, 2023;Webb, 2021). Overall, there were only 7 total studies (14.9%) that could not be classified by research phase and home advantage effect (Gouveia & Pereira, 2021;Jiang et al, 2021;Magistro & Wack, 2023;Richlan et al, 2023;Steinfeldt et al, 2022;Webb, 2021;Wilkesmann, 2022), highlighting that the vast majority of works clearly assessed impacts on home advantage.…”
Section: Variation Of Home Advantage After Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, youth and academy players might benefit from VR, as simulations of loud fan chants or in-match pressure situations (e.g., opponents running toward them at a high pace) are designed to prepare them to deal with stressful situations in senior football at an early age. As recently shown, the presence or absence of spectators in a football stadium has substantial effects on the psychological states, behavior, and performance of football players and teams (Leitner and Richlan, 2021a,b;Leitner et al, 2022;Richlan et al, 2023). This may hold even more true for less experienced and younger players, who therefore might benefit even more from this kind of VR training.…”
mentioning
confidence: 98%